Prospective study on standard and totally tubeless percutaneous nephrolithotomy - Reddy, V. Vishnu Vardhana; Repaka, Amar Kumar (International Surgery Journal, 2019)
Background: With the improvement of instrumentation and experience of percutaneous nephrolithotomy (PCNL), several modifications to the procedure have taken place in order to reduce the morbidity and early return to normal lifestyle. This study aimed to compare the totally tubeless percutaneous nephrolithotomy and standard percutaneous nephrolithotomy techniques. Methods: It is a prospective randomized, clinical trial done on 60 patients was patients older than 20 years and younger than 60 years who were chosen for elective surgery of kidney stones via the PCNL technique. Patients were divided into two groups, standard PCNL (with a nephrostomy tube) and totally tubeless PCNL (no ureter stents or ureteric catheters). Results: Demographic data is matched in two groups of patients. The mean operation time was slightly longer in the standard group (108 minutes) than in the totally tubeless group (102 minutes), but there was no statistically significant difference. There was no significant difference between the two groups with regard to serum creatinine change or blood loss. Haemoglobin drop, hospital stay, Pain score and analgesia requirement was significantly less in the totally tubeless group. 4 patients in each group had bleeding postoperatively. Only five patients developed pyrexia in the postoperative period. The differences in the need for blood transfusion and postoperative pyrexia were not found to be statistically significant. 19 in standard group and 2 patients in totally tubeless group developed urine leak, found to be statistically significant. Conclusions: Author can conclude that the tubeless procedure has fewer complications, improved postoperative patient comfort, shorter hospitalization, and a reduced need for analgesics.